2021
DOI: 10.1186/s12883-021-02402-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to prevent falls for people with multiple sclerosis, Parkinson’s disease and stroke: an umbrella review

Abstract: Background The implementation of condition-specific falls prevention interventions is proving challenging due to lack of critical mass and resources. Given the similarities in falls risk factors across stroke, Parkinson’s Disease (PD) and Multiple Sclerosis (MS), the development of an intervention designed for groups comprising of people with these three neurological conditions may provide a pragmatic solution to these challenges. The aims of this umbrella review were to investigate the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…It is promising that several of the studies included interventions based on contemporary evidence. Multidisciplinary interventions align with emerging falls prevention evidence in neurological populations, 9 and with the strong evidence from systematic reviews in older adults. 72 A recent systematic review on telehealth delivered falls prevention exercise for older adults found reduced falls rates, where the largest effect was found for a multidisciplinary intervention.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is promising that several of the studies included interventions based on contemporary evidence. Multidisciplinary interventions align with emerging falls prevention evidence in neurological populations, 9 and with the strong evidence from systematic reviews in older adults. 72 A recent systematic review on telehealth delivered falls prevention exercise for older adults found reduced falls rates, where the largest effect was found for a multidisciplinary intervention.…”
Section: Discussionmentioning
confidence: 88%
“…[5][6][7] Fear of falling is common in neurological conditions and can lead to activity avoidance and participation restrictions. 8 Among neurological populations, low-to-moderate certainty evidence indicates exercise programs targeting strength, balance or mobility reduce falls rates for people with Parkinson's disease and stroke, [9][10][11] and improves physical outcomes in multiple sclerosis. 12 Other effective interventions for reducing falls include falls risk assessments, education and environmental modifications.…”
Section: Introductionmentioning
confidence: 99%
“…O’Malley et al, for example, in a recent compilation of systematic reviews on the effectiveness of exercise-based interventions at reducing falls, identified 11 PD studies of poor to intermediate quality of evidence. The majority of evaluations found the intervention to have a significant effect on documented fall outcomes, but three found inconsistent results on both efficacy and outcomes [ 86 ]. We conclude that even though neurorehabilitation in movement disorders has made progress due to better understanding of pathophysiology and compensatory mechanisms, the rise of promising approaches, such as increased practice intensity, and the use of new technology, high quality research continues to be needed both in areas where data are abundant and in areas where they are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This will be an international, multi-perspective consensus study, which will involve five stages as demonstrated in Figure 1: 42 . This umbrella review was registered with PROSPERO (CRD42020175409) and the protocol published in an open access repository 43 .…”
Section: Designmentioning
confidence: 99%